Ada' Mappurondo, Indigenous Religion Resurgence and State Accommodation in Indonesia - Hidayat, Ferdy (Indigenous Southeast Asian and Ethnic Studies, 2025)
This article examines the resurgence of indigenous religions in Indonesia, driven by state recognition policies, particularly the Constitutional Court Decision Number 97/PUU-XIV/2016. Focusing on the Ada' Mappurondo community in Mamasa Regency, West Sulawesi Province, the study highlights how adherents, once marginalised by the state and local society, now experience significant changes due to state recognition. However, challenges persist, as their sacred traditions and spiritual practices are frequently undermined by neighbouring communities. Using a qualitative approach and literature review, this article analyses the state's accommodation efforts and their impact on citizen relations following the Constitutional Court's decision. The Ada' Mappurondo community exemplifies both informal and formal citizenship models. Informally, they recognise their limited capacity to influence government decision-making and thus do not actively pursue citizenship rights, despite benefiting from the Court's ruling. Formally, they continue to advocate for the preservation of their ancestral teachings. When local residents disrupt their spiritual practices, the Ada' Mappurondo community responds by asserting their rights. The study concludes that government-facilitated dialogue is essential to foster sustainable relationships between the Ada' Mappurondo community and local residents. Such efforts should not only address practical concerns but also ensure that the aspirations of the Ada' Mappurondo community are heard and respected, thereby strengthening intercommunity relations in the post-recognition era.